Selection of The Best Marketplace Using The Weighted Product Method (Case Study in Jabodetabek Area) - Kastilia, Elizabet Tabita; Kurniawati, Ana (Dinasti International Journal of Management Science, 2024)
The rapid growth of internet users has a major impact, especially in providing opportunities for producers and consumers to conduct business transactions online. During the Covid-19 pandemic, the marketplace can be said to be one of the businesses that has not experienced a decline like other conventional businesses. How to choose a marketplace that sells products at the cheapest price, product quality and the best online customer reviews is an interesting study to research. Research conducted on 5 marketplaces. The analytical tool used in this study uses the Weighted Product (WP) method. Tokopedia is the best marketplace that consumers can choose to shop. The marketplace with the cheapest price is owned by Blibli.com and the best online customer review is owned by Lazada.